A study of quality tools and techniques in the context of industrial revolution 4.0 in Malaysia. what’s new? - Saifuddin, Isa; Abdul Hamid, Mohd Syaiful Rizal (SRAC - Romanian Society for Quality office@srac.ro, 2020)
The purpose of this article was to explore a systematic pattern for selecting quality tools and techniques in industrial revolution 4.0 particularly in smart manufacturing context. This study asked, “What are the appropriate Quality Management tools and techniques in the context of the Industrial Revolution 4.0 particularly for smart manufacturing?” To answer this question, multiple case study and in-depth literature review were employed as the research design approach. Two key data collection methods (qualitative methods) were used: (1) Primary data from face-to-face interview with Toyo Memory Technology and Intel Malaysia (2) Secondary data from previous study. This review coupled with the case study analysis led to the identification on the real implementation of quality tools and techniques in the industries. Thus, the researchers gained the information on how the industries select the quality tools and techniques to manage quality performance in the organization and the researchers examined the association and prevalence of different quality tools and techniques in context of smart manufacturing. As a result, industrial revolution 4.0 for quality management practices might get high impact for the best performance assessment in which it is addressed in various ways, particularly there are very few studies in this area that have been conducted in the Malaysian manufacturing sector, and to recommend the best practices implemented from the managers’ perspectives. Finally, for scholars, this article can enhance their understanding of Industrial Revolution 4.0 and quality management practices as well as highlight opportunities for further research. © 2020 Elsevier B.V., All rights reserved.
Keywords: Case study; Industrial revolution 4.0; Quality management; Quality tools and techniques; Smart manufacturing